Setting up and running a small flour mill or bakery - Fellows, Peter; Axtell, Barrie (Technical Centre for Agricultural and Rural Cooperation, 2004)
The purpose of this book is to describe the activities needed to run a successful small-scale enterprise based on processing cereal grains.